Severe acute respiratory syndrome coronavirus-2 accessory proteins ORF3a and ORF7a modulate autophagic flux and Ca2+ homeostasis in yeast - Garrido-Huarte, José Luis; Fita-Torró, Josep; Viana, Rosa; Pascual-Ahuir, Amparo; Proft, Markus (Frontiers in Microbiology, 2023)
Virus infection involves the manipulation of key host cell functions by specialized virulence proteins. The SARS-CoV-2 small accessory proteins ORF3a and ORF7a have been implicated in favoring virus replication and spreading by inhibiting the autophagic flux within the host cell. Here, we apply yeast models to gain insights into the physiological functions of both SARS-CoV-2 small ORFs. ORF3a and ORF7a can be stably overexpressed in yeast cells, producing a decrease in cellular fitness. Both proteins show a distinguishable intracellular localization. ORF3a localizes to the vacuolar membrane, whereas ORF7a targets the endoplasmic reticulum. Overexpression of ORF3a and ORF7a leads to the accumulation of Atg8 specific autophagosomes. However, the underlying mechanism is different for each viral protein as assessed by the quantification of the autophagic degradation of Atg8-GFP fusion proteins, which is inhibited by ORF3a and stimulated by ORF7a. Overexpression of both SARS-CoV-2 ORFs decreases cellular fitness upon starvation conditions, where autophagic processes become essential. These data confirm previous findings on SARS-CoV-2 ORF3a and ORF7a manipulating autophagic flux in mammalian cell models and are in agreement with a model where both small ORFs have synergistic functions in stimulating intracellular autophagosome accumulation, ORF3a by inhibiting autophagosome processing at the vacuole and ORF7a by promoting autophagosome formation at the ER. ORF3a has an additional function in Ca2+ homeostasis. The overexpression of ORF3a confers calcineurin-dependent Ca2+ tolerance and activates a Ca2+ sensitive FKS2-luciferase reporter, suggesting a possible ORF3a-mediated Ca2+ efflux from the vacuole. Taken together, we show that viral accessory proteins can be functionally investigated in yeast cells and that SARS-CoV-2 ORF3a and ORF7a proteins interfere with autophagosome formation and processing as well as with Ca2+ homeostasis from distinct cellular targets.